Infection status and circulating strains of rotaviruses in Chinese children younger than 5-years old from 2011 to 2018: systematic review and meta-analysis - Jingxin Li; Hong Wang; Dandi Li; Qing Zhang; Na Liu (Taylor & Francis Group, 2021)
To evaluate rotavirus (RV) disease burden and circulating strains of RV among Chinese children younger than 5-years old who had diarrhea from 2011 to 2018. PubMed, Web of Science, Embase, CNKI and WANFANG databases were systematically searched to identify studies that reported RV prevalence in mainland China. After data extraction, a fixed-effects model or a random-effects model was applied to estimate RV positivity and proportions of G and P types. Statistical analysis was conducted using R software. We initially reviewed 1323 studies, and identified 69 studies that were eligible. The overall proportion of RV gastroenteritis (RVGE) among children under 5-years old who presented with diarrhea and sought medical care was 34.0% (95% CI: 31.3, 36.8), and RV positivity was higher among inpatients (39.7%) than outpatients (23.9%). Western areas of China had the highest proportion of RVGE (42.7%), and RV positivity was highest for children who were 6 months-old to 2 years-old. The most prevalent G types were G3 (26.1%), G9 (17.5%), and G1 (12.8%), the most prevalent P type was P[8] (56.8%) and the most prevalent G-P combination was G9P[8] (20.9%). RV continues to be a main cause of acute gastroenteritis in Chinese children who are younger than 5 years old. Following the introduction of an RV vaccine in 2011, monitoring of the disease burden of RV diarrhea and circulating strains in China remain important for assessments of vaccine efficacy.